John W. Forney papers - Forney, John W. (John Wien), 1817-1881.
Correspondence (chiefly letters of introduction and courtesy notes) and autographs collected by Forney relating to his various positions. Persons represented include Edward Bates, Montgomery Blair, Orville Hickman Browning, Simon Cameron, Salmon P. Chase, William P. Fessenden, Joseph Henry, Morton McMichael, Robert Dale Owen, Wendell Phillips, Lyman Trumbull, Thurlow Weed, and Henry Wise.
Editor, publisher, clerk of the U.S. House of Representatives, and secretary of the U.S. Senate.
Collection material in English.
Keywords: Bates, Edward, -- 1793-1869.; Blair, Montgomery, -- 1813-1883.; Browning, Orville Hickman, -- 1806-1881.; Cameron, Simon, -- 1799-1889.; Chase, Salmon P. -- 1808-1873.; Fessenden, William Pitt, -- 1806-1869.; Henry, Joseph, -- 1797-1878.; McMichael, Morton, -- 1807-1879.; Owen, Robert Dale, -- 1801-1877.; Phillips, Wendell, -- 1811-1884.; Trumbull, Lyman, -- 1813-1896.; Weed, Thurlow, -- 1797-1882.; Wise, Henry A. -- 1806-1876.; United States. -- Congress. -- House; United States. -- Congress. -- Senate; Clerks, U.S. House of Representatives; Editors; Publishers; Secretaries, U.S. Senate